posted by Rachale on .
Let f(x) = 6/x-1 and g(x) = 1+3/x. Please find the composite function of (fog)(x)
(fog)(x) is a notation for substituting g(x) for x in the definition of f(x), in other words,
(fog)(x) = f(g(x))
Using f(x) = 6/x-1
and g(x) = 1+3/x
you would find
= 6/g(x) -1
= 6/(1+3/x) - 1
So in other words the final answer would be what? I got 2x. Is this correct?
I got (5x-3)/(x+3).
Can you show me how you got 2x?
Actually, it slipped my memory:
There is probably a mis-interpretation of the parentheses:
f(x) = 6/(x-1) and g(x) = 1+3/x
f º g (x)
If this is the case, the answer is (A).